The Position of Ampi Kale' Grants in The Community of Sibulue District, Bone Regency: A Review of Islamic Inheritance Law - A. Very Febriany; Asni Zubair; Hamzah; Nur Afifah HS (Al-Bayyinah, 2026)
This study examines the practice of Ampi Kale' grants in Sibulue District by highlighting three main aspects, namely the practice of implementation, community views, and analysis of the perspective of Islamic inheritance law. The method used is empirical law with a qualitative approach, through in-depth interviews with traditional leaders, religious leaders, and the community involved in the grant, as well as a literature review of inheritance fiqh, customary law, and maqāṣid al-syarī‘ah theory. Data analysis was conducted using descriptive qualitative methods to identify patterns, meanings, and socio-religious implications of the practice. The results of the study show an empirical analysis of the Ampi Kale' practice as a customary gift phenomenon that lies at the intersection between gifts and wills in Islamic inheritance law. Thus, the meaning of Ampi Kale' has transformed from a mere moral reward to an instrument of wealth distribution that directly impacts inheritance rights. This study offers a model for harmonizing custom and Sharia by positioning Ampi Kale' as a conditional gift that must fulfill the principles of justice, willingness, and legal certainty. This study enriches the body of Islamic family law with relevant, current, and contextual local case studies, particularly regarding the integration of customary law and Islamic law in inheritance practices.